2022
DOI: 10.1038/s41598-022-13200-6
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of immune related gene expression profiles and immune cell components in patients with Barrett esophagus

Abstract: Barrett's esophagus (BE) is a well-known precancerous condition of esophageal adenocarcinoma. However, the immune cells and immune related genes involved in BE development and progression are not fully understood. Therefore, our study attempted to investigate the roles of immune cells and immune related genes in BE patients. The raw gene expression data were downloaded from the GEO database. The limma package in R was used to screen differentially expressed genes (DEGs). Then we performed the least absolute sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 42 publications
(48 reference statements)
0
1
0
Order By: Relevance
“…Moreover, an increased serum concentration of CRP was associated with a high incidence of many diseases such as chronic kidney failure, type 2 diabetes, cardiovascular disease, sarcopenia, loss of muscle mass, and strength and poor physical performance [ 41 ]. In a meta-analysis including 1370 individuals, the authors reported that patients with sarcopenia had higher concentration of CRP compared with controls [ 15 , 26 , 41 ]. Camilla et al also reported that a stronger relationship between CRP and muscle mass than IL-6 was observed in the population living in the community [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, an increased serum concentration of CRP was associated with a high incidence of many diseases such as chronic kidney failure, type 2 diabetes, cardiovascular disease, sarcopenia, loss of muscle mass, and strength and poor physical performance [ 41 ]. In a meta-analysis including 1370 individuals, the authors reported that patients with sarcopenia had higher concentration of CRP compared with controls [ 15 , 26 , 41 ]. Camilla et al also reported that a stronger relationship between CRP and muscle mass than IL-6 was observed in the population living in the community [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…During the NHANES 1999-2000, people aged 20 or older who participated in consecutive study cycles were examined. In our analysis, the exclusion criteria were participants without sufficient data to calculate DII or without H pylori immunoglobulin G information [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%